2017
DOI: 10.1111/deci.12285
|View full text |Cite
|
Sign up to set email alerts
|

Customer Differentiation with Shipping as an Ancillary Service? Free Service, Prioritization, and Strategic Delay

Abstract: A service provider/retailer offers ancillary service (e.g., shipping by an online retailer) to two types of customers, impatient and patient, who may be heterogeneous both in their delay sensitivities and service valuations. She can use prioritization and/or strategic delay to differentiate them by offering two service classes and charging different prices, potentially resulting in a split in which a single customer type selects both the classes. Her objective is to minimize cost while satisfying individual ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Pangburn & Stavrulaki (2008) juxtapose segmentation and pooling policies for revenue maximizing firms offering different services. Sainathan (2018) considers the strategies of prioritization and strategic delays within the realm of ancillary firms serving different classes of customers (patient and impatient). Some other papers on consumers' self-selection in the service and operations literature include Lederer & Li (1997), Afèche (2013), Afeche & Pavlin (2016) and Maglaras et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pangburn & Stavrulaki (2008) juxtapose segmentation and pooling policies for revenue maximizing firms offering different services. Sainathan (2018) considers the strategies of prioritization and strategic delays within the realm of ancillary firms serving different classes of customers (patient and impatient). Some other papers on consumers' self-selection in the service and operations literature include Lederer & Li (1997), Afèche (2013), Afeche & Pavlin (2016) and Maglaras et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, they do not model competition. As in this work, Sainathan (2018) also compares differentiated service with single service. However, he considers an SP offering ancillary service in which all the customers have to be satisfied while minimizing the cost of service provision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sainathan (2018) does compare prioritized and single services whilePangburn and Stavrulaki (2008) compare segmented and pooled services. However, as we explain above, their settings are different.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ComScore [8] found that 42% of online shoppers in Asia added items to their shopping carts in order to qualify for free shipping. So more and more e-commerce platforms have used free shipping to attract online consumers' shopping in order to improve the platforms' performance [9,10]. However, the loss due to free transportation is so huge that the promotion is not profitable.…”
Section: Literature Reviewmentioning
confidence: 99%